TI_GERICHTE 35.2024.48 vom 19. August 2024 , Infortunio alla spalla sinistra. Status quo sine. Rinvio per perizia ex art. 44 LPGA - TI Tribunale d'appello (2024)
Infortunio alla spalla sinistra. Status quo sine. Rinvio per perizia ex art. 44 LPGA